Effectiveness of Boswellia and Boswellia extract for osteoarthritis patients: a systematic review and meta-analysis - Ganpeng Yu; Wang Xiang; Tianqing Zhang; Liuting Zeng; Kailin Yang; Jun Li (BMC, 2020)
Abstract Background Osteoarthritis (OA) is the commonest form of inflammatory joint disease. Unfortunately, to date, there is no appropriate treatment for OA. Boswellia serrata was considered as a potent anti-inflammatory, anti-arthritic and analgesic agent that may be a drug for OA. Methods In this meta-analysis, data from randomized controlled trials were obtained to assess the effects of Boswellia or its extract versus placebo or western medicine in patients with OA. The primary outcomes included visual analogue score (VAS), WOMAC pain, WOMAC stiffness, WOMAC function and lequesne index. Result Seven trials involving 545 patients were included. Compared with the control group, Boswellia and its extract may relieve the pain [VAS: (WMD -8.33; 95% CI -11.19, − 5.46; P<0.00001); WOMAC pain: (WMD -14.22; 95% CI -22.34, − 6.09; P = 0. 0006)] and stiffness [WOMAC stiffness: (WMD -10.04; 95% CI -15.86, − 4.22; P = 0. 0007)], and improve the joint's function [WOMAC function: (WMD -10.75; 95% CI -15.06, − 6.43; P<0. 00001); lequesne index: (WMD -2.27; 95% CI -3.08, − 1.45; P<0. 00001)]. Conclusion Based on current evidence, Boswellia and its extract may be an effective and safe treatment option for patient with OA, and the recommended duration of treatment with Boswellia and its extract is at least 4 weeks.